Increased HRD score in cisplatin resistant penile cancer cells - Winkelmann, Ria; Bankov, Katrin; Döring, Claudia; Cinatl, Jaroslav; Grothe, Sebastian; Rothweiler, Florian; Michaelis, Martin; Schmitt, Christina; Wild, Peter J.; Demes, Melanie; Cinatl, Jindrich; Vallo, Stefan (BMC cancer, 2022)
Background/Introduction Penile cancer is a rare disease in demand for new therapeutic options. Frequently used combination chemotherapy with 5 fluorouracil (5-FU) and cisplatin (CDDP) in patients with metastatic penile cancer mostly results in the development of acquired drug resistance. Availability of cell culture models with acquired resistance against standard therapy could help to understand molecular mechanisms underlying chemotherapy resistance and to identify candidate treatments for an efficient second line therapy. Methods We generated a cell line from a humanpapilloma virus (HPV) negative penile squamous cell carcinoma (UKF-PEC-1). This cell line was subject to chronic exposure to chemotherapy with CDDP and / or 5-FU to induce acquired resistance in the newly established chemo-resistant sublines (PEC-1 r CDDP 2500 , adapted to 2500 ng/ml CDDP; UKF-PEC-1 r 5-FU 500 , adapted to 500 ng/ml 5- FU; UKF-PEC1 r CDDP 2500 / r 5-FU 500 , adapted to 2500 ng/ml CDDP and 500 ng/ml 5 -FU). Afterwards cell line pellets were formalin-fixed, paraffin embedded and subject to sequencing as well as testing for homologous recombination deficiency (HRD). Additionally, exemplary immunohistochemical stainings for p53 and gammaH2AX were applied for verification purposes. Finally, UKF-PEC-1 r CDDP 2500 , UKF-PEC-1 r 5-FU 500 , UKF-PEC1 r CDDP 2500 / r 5-FU 500 , and UKF-PEC-3 (an alternative penis cancer cell line) were tested for sensitivity to paclitaxel, docetaxel, olaparib, and rucaparib. Results and conclusions The chemo-resistant sublines differed in their mutational landscapes. UKF-PEC-1 r CDDP 2500 was characterized by an increased HRD score, which is supposed to be associated with increased PARP inhibitor and immune checkpoint inhibitor sensitivity in cancer. However, UKF-PEC-1 r CDDP 2500 did not display sensitivity to PARP inhibitors.